Association Between Midwifery Students' Awareness of Global Climate Change and Their Attitudes and Behaviours Toward Medical Waste - Sultan Esra Sayar (Nursing Open, 2026)
ABSTRACT Aim This study aimed to determine whether midwifery students' awareness of global climate change is associated with their attitudes and behaviours toward medical waste management. Design This study employed a descriptive cross‐sectional design. Methods The study was conducted during the 2025–2026 academic year at Atatürk University. The sample consisted of volunteer midwifery students enrolled across all academic years. Data were collected using a sociodemographic questionnaire, the Global Climate Change Awareness Scale and the Medical Waste Attitude and Behaviour Scale. Data were analysed using descriptive statistics, independent samples t ‐tests, one‐way ANOVA with Bonferroni post hoc tests and Pearson correlation analysis. Results Participants demonstrated high levels of climate change awareness (74.60 ± 8.21) and generally positive attitudes toward medical waste management (96.91 ± 12.10). Fourth‐year students had significantly higher awareness scores than students in lower academic years ( p < 0.05). Students who perceived climate change as a professional responsibility and believed that it affected health had significantly higher climate change awareness scores. A moderate positive correlation was identified between climate change awareness and medical waste attitudes ( r = 0.392, p < 0.001). Implications for Nursing Practice Nurse educators should integrate climate change, environmental sustainability and medical waste management into undergraduate nursing and midwifery curricula using evidence‐based educational strategies. Strengthening students' environmental competencies may promote sustainable healthcare practices, improve waste management behaviours and prepare future healthcare professionals to address the environmental challenges associated with climate change. No Patient or Public Contribution No patient or public contribution.